Cultivating Sustainability: Exploring the Relationship between Homestead Gardening, Land Property, and Family Economic Pressure in Household with Stunting Children - Barai, Sultan Azis; Nurmahfuzhah, Nisrina; -, Defina (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The impacts of climate change exacerbate the problems of food insecurity and malnutrition, especially child stunting. This study aims to characterize households with stunted children and explore the relationship between yard agroecosystem management strategies, yard ownership, and family economic stress. The study was conducted among 68 households with stunted children in Sumedang District, West Java, selected using purposive sampling. The results found that only 11.7 percent had a dedicated yard with a low level of cultivation and utilization of agrobiodiversity. Correlation analysis showed that the husband's education level was significantly positively associated with yard ownership and utilization. The husband's age and family size were significantly positively related to objective economic pressure. The wife's education and per capita income were significantly negatively related to objective economic pressure. Meanwhile, subjective economic pressure was significantly negatively related to per capita income and significantly positively related to objective economic pressure.